2018
DOI: 10.15408/ijee.v4i1.4837
|View full text |Cite
|
Sign up to set email alerts
|

Peer-Discussion in TOEFL Preparation Class

Abstract: The aim of this study was to see whether the technique of peer-discussion during the TOEFL preparation class benefits the students in increasing their score in Section Two of TOEFL Test,  Structure and Written Expression. According to Porter et al. (2001), during the process of students’ interaction with their peer(s), students have more open chances to ask conceptual questions; and as their peer(s) respond, they can understand more correctly and individually the questions. This study adopted quasi-experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Regarding the above-mentioned issues, many studies suggested a preparation class as an ideal solution to deal with the problems (Akmal et al, 2020;Alek et al, 2019;Ismail & Wahyuni, 2018;Manan et al, 2020;Masfufah, 2018;Mousavi et al, 2014;Roza, 2019;Simanjuntak, 2018;Sudrajat & Astuti, 2018;Suryani, 2021). There are at least three primary reasons why a preparation class can increase students' scores including improving students' understanding of the materials, reducing students' stress and anxiety levels, and providing effective strategies in answering each section.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the above-mentioned issues, many studies suggested a preparation class as an ideal solution to deal with the problems (Akmal et al, 2020;Alek et al, 2019;Ismail & Wahyuni, 2018;Manan et al, 2020;Masfufah, 2018;Mousavi et al, 2014;Roza, 2019;Simanjuntak, 2018;Sudrajat & Astuti, 2018;Suryani, 2021). There are at least three primary reasons why a preparation class can increase students' scores including improving students' understanding of the materials, reducing students' stress and anxiety levels, and providing effective strategies in answering each section.…”
Section: Introductionmentioning
confidence: 99%
“…PBT is kind of TOEFL that being focused in this study. Listening, structure and written expression, and reading are the three elements of the paper-based test (Ismail & Wahyuni, 2018). The Test of Written English (TWE) is used at several colleges to assess writing abilities, although it is still uncommon in Indonesia (Ismail & Wahyuni, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The computer-based and internet-based examinations, on the other hand, offer more complex test instructions since they include all skills-speaking, listening, reading, and writing (Ismail & Wahyuni, 2018). In addition, in these two forms of TOEFL examinations, integrated teaching models are used (Ismail & Wahyuni, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their TOEFL scores have improved from 439, 34 to 506,6 within one year. As for Ismail and Wahyuni (2018) for advanced students, peer-discussion might not work very well compared to the beginners. The situation is not so different in Vietnam from the overall context world-wide.…”
mentioning
confidence: 99%